The show must go on: Effects of the COVID-19 experience on concert and music festival attendance intentions - Borromeo, Erika Belle Luces (Animo Repository, 2022)
The business of live music had been at its peak performance prior to early 2020. It has grown to become the industry's largest sector as it has become the primary source of income for both local and international musicians. In the Philippines, the industry is able to contribute roughly 7% of the country's GDP. However, the live music industry was massively disadvantaged when concert and music festival operations came to a halt due to the dramatic increase in COVID-19 cases globally. The World Health Organization has set minimum health and safety protocols including the prohibition of mass gatherings. As a result, various concerts and music festivals have been forced to cancel or postpone their events, pressuring the many key players of the industry financially. This phenomenon has piqued the researchers’ interest in probing the effects of the COVID-19 experiences on the attendance intentions on concerts and music festivals. As the independent variable of this study, the Dual Process Model of Bereavement used in the context of the COVID-19 pandemic provides two classifications for negative and positive experiences, namely Loss-Oriented and Restoration-Oriented. The attendance intentions refer to people's intentions in attending live concerts and music festivals following the pandemic, which is the study's dependent variable. The Theory of Planned Behavior was utilized to understand and predict behavioral domains of attendance intention. Combining Loss-Oriented and Restoration-Oriented COVID-19 experiences with the Attendance Intention on live music events depicts the operational framework of this study which aims to identify the effect of the COVID-19 experiences on the intention to attend live concerts and music festivals. Utilizing a mixed- method research, 445 respondents residing in Metro Manila from ages 18-37 were enjoined for an online survey and an additional 20 experienced concertgoers were interviewed virtually to provide supplementary insights and substantiate the obtained data. Subsequent findings of the conducted regression analyses show that individually and collectively, Loss-Oriented and Restoration-Oriented Experiences have a significant and positive effect on the attendance intention on live music events. It was also identified that a notable 95% of the respondents still favor live concerts over their virtual alternatives, attributing it to the unparalleled value of the physical experience. Furthermore, the pattern matching confirms that people's intentions to attend live music events remain despite the positive and negative experiences individuals had during the pandemic, noting that health and safety are factors significantly considered more than ever. In view of this, the recommendations of the study were grounded on providing different modalities of holding concerts and music festivals, mainly categorized as Live Music Events, Virtual Concerts, and Hybrid Music Events. This enables the restoration of the live music industry by emphasizing the need to adapt to concertgoers’ shifting consumption patterns. The review of hybrid events as an alternative to having live concerts at full capacity, virtual concerts, or no concerts at all, opens many possibilities for the Philippine live music industry to increase revenue streams, from both live and virtual ticket sales – enabling the restoration of the live music industry by adapting to concertgoers’ shifting consumption patterns. Keywords: COVID-19 pandemic, COVID-19 experiences, attendance intentions, concerts, music festivals, live music industry, Metro Manila